-3(n+7)=12

Simple and best practice solution for -3(n+7)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(n+7)=12 equation:


Simplifying
-3(n + 7) = 12

Reorder the terms:
-3(7 + n) = 12
(7 * -3 + n * -3) = 12
(-21 + -3n) = 12

Solving
-21 + -3n = 12

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + -3n = 12 + 21

Combine like terms: -21 + 21 = 0
0 + -3n = 12 + 21
-3n = 12 + 21

Combine like terms: 12 + 21 = 33
-3n = 33

Divide each side by '-3'.
n = -11

Simplifying
n = -11

See similar equations:

| 4--2v=10 | | 28x^2-22x+4=0 | | g/10-20=-19 | | x=(6x+8) | | 3318.1008=2*33.24*r^2+2*3.13*r*36.5 | | w^2-6w-22=-25+w^2 | | 10+2k=18 | | 9k+2=13 | | 0=.01x^2+.7x+6.1 | | 3x+31.5=123 | | w/7+43=46 | | 2s-9=3 | | w^2-6w-22=-25w^2 | | 2(-4+7x)=6x-6+30 | | X+20+2x-5=50 | | 2s-1=1 | | 3y-30=2x | | 2(2y+2)+3y=19 | | 2d+6=16 | | -x+10=-x+14 | | x=(7x+6) | | 3f-3=6 | | 36=9+9s | | (-.01x^2)+.7x+6.1=y | | 24(6)+4x=180 | | y=7x+13forx | | x^2+0.25=1.25 | | Y=-2x^2+12x-3 | | 2(4x+8)=7x+6+14 | | r^2-19r=-7r+64 | | 6x-7+4x+23=45 | | 6x-7+4x+23=10 |

Equations solver categories